The Use of PowerPoint Media for Training Participants' Learning Motivation in Ambon Religious Education and Training Centers - Djuma, La (Balai Diklat Keagamaan Ambon, 2022)
This article aims to provide a description of the development of the use of powerpoint media which is related to the learning motivation of the training participants and to continue the link in a special scope at the Ambon Religious Education and Training Center. The method used is the study of literature related to powerpoint media and learning motivation. What this article wants to convey is that the study of the use of PowerPoint media in the world of training is very promising because it is very closely related to the world of training in the formation of quality human resources.